Expediente - Horizonte, Belo Horizonte, v 12, n. 34, abr./jun. 2014 - Baptista, Paulo Agostinho Nogueira (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2014)
Expediente - Horizonte, Belo Horizonte, v 12, n. 34, abr./jun. 2014.